A Case Report: Nager Acrofacial Dysostosis - Abdollahi Fakhim, Shahin (Mashhad University of Medical Sciences, 2012)
INTRODUCTION: Nager syndrome is a malformation resulting from problems in the development of the first and second branchial arches and limb buds. The cause of the abnormal development of the pharyngeal arches in Nager syndrome is unknown. It is also unclear why affected individuals have bone abnormalities in their arms and legs. Nager syndrome is thought to have an autosomal recessive inheritance pattern when unaffected parents have more than one affected child. The purpose of this report is to present a case of Nager syndrome where the patient exhibited upper limb shortening, an unusual feature that has been reported as coexisting in some individuals with Nager syndrome. CASE REPORT: A 3.5-year-old girl was referred to our Department of Pediatric Otorhinolaryngology due to a cleft palate. Her craniofacial anomalies included malar hypoplasia, severe mandibular hypoplasia with retrognathia, downward slanted palpebral fissures, a high narrow hard palate, absent soft palate, small retroplaced tongue, bilateral external auditory canal atresia, and dysplastic ears. There was no evidence of mental retardation. Based on the craniofacial characteristics and the coexisting upper limb preaxial anomalies, a diagnosis of Nager syndrome was confirmed. CONCLUSION: Nager syndrome is a rare disorder resulting from developmental abnormalities of the first and second branchial arches. It is linked to five other similar syndromes: Miller syndrome, Treacher-Collins, Pierre-Robin, Genee-Wiedemann, and Franceschetti-Zwahlen-Klein. Multidisciplinary management by a craniofacial team is needed. Early intervention, intensive education, new surgical techniques, and an emphasis on coordinated care have improved the quality of life in this patient with Nager syndrome.